Studies on microwave steam distillation process for extraction of lemongrass essential oil - CLAUDIA K.L; Dr. Prince M.V (Guide) (Tavanur 2017 DEPARTMENT OF FOOD AND AGRICULTURAL PROCESS ENGINEERING)
Studies on microwave steam distillation process for extraction of lemongrass essential oil
Studies on microwave steam distillation process for extraction of lemongrass essential oil